Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3354/meps09338
|View full text |Cite
|
Sign up to set email alerts
|

Elevated size and body condition and altered feeding ecology of the grouper Cephalopholis argus in non-native habitats

Abstract: In 1956, the shallow-water grouper Cephalopholis argus was introduced from Moorea (French Polynesia), where grouper diversity (14 species) is high, to the Main Hawaiian Islands (MHI), where only 2 rare native deep-water groupers occur. In this non-native environment, the species has flourished and has become the dominant apex predator on many reefs. In the present study, a comparison of non-native populations of C. argus in the MHI with native populations in Moorea showed that mean total length (32.0 vs. 26.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…There were, however, two notable predator species that disproportionately affected rare prey species and significantly lowered rarefied diversity: the dottyback Pseudochromis fuscus (Almany et al 2007) and peacock grouper Cephalopholis argus . From a conservation perspective, this disproportionate effect on rare species is particularly concerning in the case of the peacock grouper, because this non-native mesopredator, introduced to Hawaii in the mid-1950s, now constitutes more than 80% of the large piscivore biomass in some locations (Meyer and Dierking 2011). The unique effects of these two species suggest we need to further study the foraging behavior of mesopredators and in particular their functional responses (sensu Stier et al 2013a;Stier and White 2014), because predators with a preference for rare species and a Type I or II functional response can destabilize prey population dynamics and catalyze reductions in reef biodiversity (White et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were, however, two notable predator species that disproportionately affected rare prey species and significantly lowered rarefied diversity: the dottyback Pseudochromis fuscus (Almany et al 2007) and peacock grouper Cephalopholis argus . From a conservation perspective, this disproportionate effect on rare species is particularly concerning in the case of the peacock grouper, because this non-native mesopredator, introduced to Hawaii in the mid-1950s, now constitutes more than 80% of the large piscivore biomass in some locations (Meyer and Dierking 2011). The unique effects of these two species suggest we need to further study the foraging behavior of mesopredators and in particular their functional responses (sensu Stier et al 2013a;Stier and White 2014), because predators with a preference for rare species and a Type I or II functional response can destabilize prey population dynamics and catalyze reductions in reef biodiversity (White et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Abundance of coral-reef mesopredators (e.g., small-bodied groupers and snappers) has also increased through the introduction of non-native predators. In some cases, these introduced predators have become extremely successful, for example, the intentionally introduced peacock grouper (Cephalopholis argus) in Hawaii (Meyer and Dierking 2011) and the accidentally introduced Pacific lionfishes (Pterois volitans and Pterois miles) in the Atlantic and Caribbean (Côté et al 2013) have each become numerically dominant mesopredators in their respective invaded communities. Because predation is known to be a key driver of ecosystem and evolutionary dynamics (Hixon 1991(Hixon , 2015, these fishing-and invasion-associated shifts in the abundance and biomass of predators are considered cause for concern among coral-reef managers and conservation practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior requires suitable habitat as the availability of prey resources have been shown to increase with both habitat composition and complexity (Ruttenberg et al 2005, Shibuno et al 2008. Therefore, it is not surprising that C. argus is typically found in coral rich habitats and feeds primarily on small, reef-associated fishes (Meyer & Dierking 2011). By extension it is expected that fishes will be more robust, grow to larger sizes, and live to greater ages when there are more resources and/or preferable habitats.…”
Section: Discussionmentioning
confidence: 99%
“…In Hawaii, the diet of C. argus is composed of fishes across a wide range of taxa, including acanthurids, holocentrids, and chaetodontids among many others (Dierking et al 2009). A study found that length, weight, and body condition were significantly greater for C. argus in Hawaii than in a native South Pacific population, indicating competitive release (Meyer & Dierking 2011).…”
Section: Study Speciesmentioning
confidence: 99%
“…This has certainly been in part because the WHFC has set aside about 35% of the coast as reserves, but it is possibly also because larger individuals are left for population replenishment. In addition, the introduced predator Cephalopholis argus cannot efficiently prey on larger individuals (Meyer and Dierking 2011). Slot-limit fishing and predation may both be occurring and contributing to a sustainable fishery.…”
Section: West Hawaii Ornamental Fisheriesmentioning
confidence: 99%